Ensino de Ciências inclusivo para surdos: uma proposta reflexiva de recurso pedagógico voltado para os anos finais do Ensino Fundamental - COELHO, Evene Thais Austriaco (2023)
This research is a case study about the educational inclusion of deaf students in the teaching and learning process of Natural Sciences, which takes place in Elementary Schools (final years) in the city of Codó (MA). The general objective was to investigate the direction of Science teaching from the perspective of teachers and sign language interpreters working in schools in Codó (MA), aiming at the elaboration of an inclusive didactic resource for the deaf. As a result of the Covid-19 pandemic, contact with schools and research collaborators took place in a hybrid way and data collection instruments were sent through virtual social communication tools (E-mail and WhatsApp). The locus of study was constituted by the pole of Elementary Schools (final years) inserted in the urban area of the city of Codó. The research participants were Science teachers and Libras interpreters working in the selected public schools. As a theoretical basis and support for the analyses, the following authors were used: Goldfeld (1997), Mantoan (2003), Ramos (2016), Carvalho (2014), Gesser (2012), Quadros (2019), Skliar (2015), Honora (2014), Lacerda et al. (2021), Chassot (2003), Carvalho (2020), Cachapuz et al. (2015), Delicoizov and Angotti et al. (2018), Krasilchick (2000) and among others. As for the research methodology, it followed a qualitative and quantitative approach in education, based on the analysis of two questionnaires. Content analysis was carried out, which consisted of removing the meaning units for the construction of a systemic network for data representation. From the analyses, it can be identified that inclusion is gradually being carried out in public schools in Codó. However, it was found that Science teachers still feel insecure about inclusion. Emphasis was placed on the importance that should be given to encouraging training for teachers and the provision of didactic resources aimed at improving the quality of education offered to students with disabilities, such as deaf students. It is hoped that the elaboration of the paradidactic book Tina, the curious and the chlorophyllated beings and the Pedagogical Handbook Guide can contribute to deaf students and Science teachers, encouraging new research and academic productions.